The Burden and Trend of Blood-Borne Pathogens among Asymptomatic Adult Population in Akwatia: A Retrospective Study at the St. Dominic Hospital, Ghana - Sylvester Yao Lokpo; Mavis Popuelle Dakorah; Gameli Kwame Norgbe; James Osei-Yeboah; Godwin Adzakpah; Isaac Sarsah; John Gameli Deku; Innocent Afeke; Emmanuel Akomanin Asiamah; Nana Yaw Barimah Manaphraim; Isaac Asare; Bright Justice Ayidzoe; et al. (Journal of Tropical Medicine)
Background. This study was aimed at evaluating the seroprevalence and trend of blood-borne pathogens (HIV, HCV, HBV, and Syphilis) among asymptomatic adults at Akwatia during a four-year period (2013–2016). Materials and Methods. The study was a retrospective analysis of secondary data of blood donors who visited the hospital from January 2013 to December 2016. Archival data from 11,436 prospective donors was extracted. Data included age, sex, and place of residence as well as results of infectious markers (HIV, HBV, HCV, and Syphilis). Results. The prevalence of blood-borne pathogens in the donor population was 4.06%, 7.23%, 5.81%, and 10.42% for HIV, HBV, HCV, and Syphilis infections, respectively. A significant decline in HBV and HCV infections was observed in the general donor population and across genders. HIV infection rate remained steady while Syphilis infections recorded a significantly increasing trend, peaking in the year 2015 (14.20%). Age stratification in HBV infection was significant, peaking among age group 40–49 years (8.82%). Conclusion. Asymptomatic blood-borne pathogen burden was high among the adult population in Akwatia. Gender variations in HBV, HCV, and Syphilis infections in the cumulative four-year burden were observed. Awareness needs to be created, especially in the older generation.